The polySUMOylation axis promotes nucleolar release of Tof2 for mitotic exit - Emily Gutierrez-Morton; Cory Haluska; Liam Collins; Raed Rizkallah; Robert J. Tomko, Jr.; Yanchang Wang (Cell Reports, 2024)
Summary: In budding yeast, the nucleolus serves as the site to sequester Cdc14, a phosphatase essential for mitotic exit. Nucleolar proteins Tof2, Net1, and Fob1 are required for this sequestration. Although it is known that these nucleolar proteins are SUMOylated, how SUMOylation regulates their activity remains unknown. Here, we show that Tof2 exhibits cell-cycle-regulated nucleolar delocalization and turnover. Depletion of the nuclear small ubiquitin-like modifier (SUMO) protease Ulp2 not only causes Tof2 polySUMOylation, nucleolar delocalization, and degradation but also leads to Cdc14 nucleolar release and activation. This outcome depends on polySUMOylation and the activity of downstream enzymes, including SUMO-targeted ubiquitin ligase and Cdc48/p97 segregase. We further developed a system to tether SUMO machinery to Tof2 and generated a SUMO-deficient tof2 mutant, and the results indicate that Tof2 polySUMOylation is necessary and sufficient for its nucleolar delocalization and degradation. Together, our work reveals a polySUMO-dependent mechanism that delocalizes Tof2 from the nucleolus to facilitate mitotic exit.